2016
DOI: 10.1590/1806-9282.62.01.38
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, fatigue and quality of life in breast cancer patients

Abstract: Objective: to evaluate the relationship between levels of physical activity, fatigue and quality of life (QOL) in women diagnosed with breast cancer. Methods: 215 women between the ages of 40 and 65 years were recruited at a cancer clinic. Physical activity levels were assessed by using the International Physical Activity Questionnaire (IPAQ), fatigue levels by using the revised Piper scale, and QOL by means of EORTC QLQ-C30 and WHOQOL-Bref. Statistical analysis was performed using Minitab statistical software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 14 publications
2
30
0
13
Order By: Relevance
“…Canário et al (2016) [13] conducted a study in the state of Rio Grande do Norte, which corroborates our findings. A high prevalence of the symptoms mentioned above was found, therefore affecting the physical domain.…”
Section: Discussionsupporting
confidence: 91%
“…Canário et al (2016) [13] conducted a study in the state of Rio Grande do Norte, which corroborates our findings. A high prevalence of the symptoms mentioned above was found, therefore affecting the physical domain.…”
Section: Discussionsupporting
confidence: 91%
“…Their results showed that: The hypothesized model provided a good fit in the full sample (χ 21 The results of our study were consistent with the results of this study too. Also, the randomized intervention trial of Schmidt et al 22 (2014) in breast cancer patients indicated a beneficial impact of resistance exercise Other similar research to our study, carried out by Canário et al 23 in 2016 .They evaluated the relationship between levels of physical activity, fatigue and quality of life (QOL) in women diagnosed with breast cancer. 215 women between the ages of 40 and 65 years were recruited at a cancer clinic.…”
Section: Discussionsupporting
confidence: 69%
“…They concluded: physical activity appears to positively influence fatigue and QOL in women diagnosed with breast cancer. 23 Saarto et al 24 in 2012 conducted a randomized trial entitled; effectiveness of a 12-month exercise program on physical performance and quality of life of breast cancer survivors. A total of 573 breast cancer survivors were assessed 12 months after adjuvant treatments by means of a 2 km walk, run test, physical fitness and QOL evaluation (EORTC).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the impact of PA on fatigue and QoL requires accounting for the complexity and evolution of PA over time. However, these conditions are often not considered . In a cross‐sectional study, PA improved QoL and reduced fatigue in women with BC, but the evolution of PA was not studied .…”
Section: Introductionmentioning
confidence: 99%